Developing a nomogram-based scoring model to estimate the risk of pulmonary embolism in respiratory department patients suspected of pulmonary embolisms - Lanfang, Feng; Xu, Ma; Jun, Chen; Jia, Zhao; Wenchen, Li; Xinghua, Jia (Frontiers in Medicine, 2023)
Objective: Pulmonary embolisms (PE) are clinically challenging because of their high morbidity and mortality. This study aimed to create a nomogram to accurately predict the risk of PE in respiratory department patients in order to enhance their medical treatment and management. Methods: This study utilized a retrospective method to collect information on medical history, complications, specific clinical characteristics, and laboratory biomarker results of suspected PE patients who were admitted to the respiratory department at Affiliated Dongyang Hospital of Wenzhou Medical University between January 2012 and December 2021.This study involved a total of 3511 patients who were randomly divided into a training group (6 parts) and a validation group (4 parts) based on a 6:4 ratio. The LASSO regression and multivariate logistic regression were used to develop a scoring model using a nomogram. The performance of the model was evaluated using receiver operating characteristic curve (AUC), calibration curve, and clinical decision curve. Results: Our research included more than 50 features from 3511 patients. The nomogram-based scoring model was established using 6 predictive features including age, smoke, temperature, systolic pressure, D-dimer and Fibrinogen, which achieved AUC values of 0.742 in the training cohort (95% CI 0.720-0.765) and 0.724 in the validation cohort (95% CI 0.695-0.753). The results of the calibration curve revealed a strong consistency between probability predicted by the nomogram and actual probability. The decision curve analysis (DCA) also demonstrated that the nomogram-based scoring model produced a favorable net clinical benefit. Conclusions: In this study, we successfully developed a novel numerical model that can predict the risk of PE in respiratory department patients, which can not only appropriately select PE prevention strategies but also decrease unnecessary Computed tomographic pulmonary angiography (CTPA) scans and their adverse effects.